Constitutional Identity Versus “Ever Closer Union” from the Perspective of a Central – Eastern European Country: Poland - Pastuszko, Grzegorz (Maastricht 30: A Central European Perspective, 2025)
This article is devoted to one of the most important aspects of Poland’s membership in the European Union. Strictly speaking, it aims to answer the question of what the constitutional identity of the Republic of Poland is as a member state in the context of the treaty formula “ever closer union”. The following chapters of the study analyze the following issues: the concept of “ever closer union” and the historicaldevelopment of the EU, “Ever closer union” and the constitutional identity of the Third Republic of Poland in the pre-accession period, “Ever closer union” and the constitutional identity of the Third Republic of Poland in the post-accession period, “Ever closer union” during the Lisbon Treaty period. The key research conclusion indicates variability, but also differences of opinion, in the perception of the conceptof constitutional identity in Polish conditions.Keywords: Ever closer union, constitutional identity, Poland, European Union